Soviet and British diplomacy at international conferences on the eve of the formation of the USSR - E. Yu. Sergeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines the formation of the Soviet state and its place within the European international relations system in the first half of the 1920s both in the context of new principles of interstate and economic interactions and geopolitical transformations triggered by the First World War. In the case of Soviet Russia, the latter implied the need to break international isolation and economic blockade which pushed Soviet leaders to intensify efforts to restore economic and political ties with the Western states after the Civil War and intervention. The paper focuses on the peripeteias of interaction between the Soviet and British diplomacy at the key international summits of 1922 — the Genoa, the Hague, and the Lausanne conferences. Drawing on a wide range of primary sources from the Russian and British archives, as well as the memoirs of the participants, their official and personal correspondence, the author examines the achievements and miscalculations of Moscow and London in attempts to stabilize the Versailles-Washington world order on the eve and during these conferences. The author emphasizes that the Kremlin managed to pave the way for the diplomatic recognition of the Bolshevik regime by the leading powers and to take part in the discussion on Black Sea straits regime, while Whitehall managed to strengthen imperial positions both in Europe and in the Middle East, although the prospects of rapprochement between Moscow and Berlin and Ankara remained a major concern for the Foreign Office. However, these conferences failed to address the issue of Russian debts and it continued to be an obstacle to the normalization of bilateral relations. The author highlights a number of other significant factors that affected the outcomes of the conferences: the lack of a coordinated foreign policy approaches both among the Bolsheviks and within the British government, the persistence of stereotypes about the Bolsheviks, as well as an emerging trend towards rapprochement between the vanquished and the revisionist states which was particularly dangerous for the Versailles-Washington order. As for the outcomes of the diplomatic rivalry between Moscow and London, the author concludes that these conferences provided the parties with an invaluable opportunity to discuss the key issues of bilateral relations and European big politics and can rightfully be considered an important step in the development of the post-war international relations from confrontation to constructive interaction.